Communication Versus Geography : The Case Study of Sarawak Homestay Operator Association - Shaik Azahar, Bin Shaik Hussain; Farid Ismeth, Syamsul Bahri (UNIMAS Publisher, 2018)
Homestay is being developed throughout the decades making it as one of the best tourism product in Malaysia. The increasing number of homestay in Sarawak each year is challenging the communication among each other administratively. Communication among all the homestay is vital in order for the information could be reached in a timely manner. Without a proper communication media used to communicate, a lot of important information could be missed out causing some of the homestays to be left out. This research is conducted to study the communication used among the homestay operators using both quantitative and qualitative methods. Interviews are conducted with the representatives of Sarawak Homestay Operator Association (SHOA) and questionnaires are distributed to the homestay operators in gathering the information. Locations could not be changed as locations are the unique selling point of a homestay and recommendations can be addressed to have mobile communication towers within the vicinity of the homestays to improve the signals. It is revealed that communication issues could be resolved if operators are actively involved as there are a variety of apps available in the market for these operators to choose from